Evidence of the niche expansion of crofton weed following invasion in China. Issue 1 (6th January 2023) - Xian, Xiaoqing; Zhao, Haoxiang; Wang, Rui; Zhang, Hongbin; Chen, Baoxiong; Liu, Wanxue; Wan, Fanghao
Abstract: Niche dynamics of invasive alien plants (IAPs) play pivotal roles in biological invasion. Ageratina adenophora —one of the most aggressive IAPs in China and some parts of the world—poses severe ecological and socioeconomic threats. However, the spatiotemporal niche dynamics of A. adenophora in China remain unknown, which we aimed to elucidate in the present study. China, Mexico; using a unifying framework, we reconstructed the climate niche dynamics of A. adenophora and applied the optimal MaxEnt model to predict its potential geographical distribution in China. Furthermore, we compared the heterogeneity of A. adenophora niche between Mexico (native) and China (invasive). We observed a low niche overlap between Mexico (native) and China (invasive). Specifically, the niche of A. adenophora in China has distinctly expanded compared to that in Mexico, enhancing the invasion risk of this IAP in the former country. In fact, the climatic niche of A. adenophora in Mexico is a subset of that in China. The potential geographical distribution of A. adenophora is concentrated in the tropical and subtropical zones of Southwest China, and its geographical distribution pattern in China is shaped by the combination of precipitation and temperature variables. The niche dynamics of A. adenophora follow the hypothesis of niche shift and conservatism. The present work provides a unifying framework for studies on the niche dynamics of other IAPs worldwide. Abstract : Using a unifying framework, we reconstructed the climate niche dynamics of A. adenophora and applied the optimal MaxEnt model to predict its potential geographical distribution in China. Furthermore, we compared the heterogeneity of its niche between Mexico (native) and China (invasive).